CONNECTIVE TISSUE DISEASES: FOCUS ON MICROCIRCULATORY BED - Zarudna, O. I.; Venher, I. K.; Dovbush, A. V. (International Journal of Medicine and Medical Research, 2020)
Background. A microcirculatory bloodstream is a target, source and reason of the pathological process in patients with systemic connective tissue diseases. Objectives. This study is focused on meta-analyses of biopsy material of skin flaps harvested from patients’ fingers to identify specific morphological changes. Methods. A retrospective analysis of the medical records of 39 examinees with systemic sclerosis (SSc), 45 with Systemic Lupus Erythematosus (SLE), and 45 with rheumatoid arthritis (RA) was performed. The condition of peripheral hemodynamics was examined with longitudinal rheovasography of arms and legs. Endothelin-1 (ЕТ1) concentration was evaluated by immunoenzymatic method. We assessed other results of clinical and laboratory tests to compare them with morphological changes of the microcirculatory bed. Results. Most patients involved suffered from abnormal peripheral hemodynamics. It was revealed that kidneys, lungs or heart were damaged more frequently in the patients with peripheral blood circulation disorders, which were the most significant in the patients with SSc (p<0.05). Disorders of peripheral blood flow were exacerbated in case of lengthening of the disease course. Concentration of ЕТ1 was relevantly higher in the patients with peripheral blood flow disorders. Number of pathologic capillaries was the highest in the SSc patients. Conclusions. In terms of integral estimation, extremely significant changes of microcirculatory bloodstream were evidenced in the patients with SSc. However, some morphometric peculiarities were revealed in the patients without peripheral blood flow disorders. Thus, normal rheovasography did not exclude any microcirculation disorders.